THEMATIC TRENDS IN SOCIAL ENTREPRENEURSHIP AND CROWDFUNDING: A BIBLIOMETRIC ANALYSIS - Arotile , Omolabake Damilola; Thiagarajan , Senthil Kumar; Agbi, Eniola Samuel (International Journal of Allied Sciences (IJAS), 2025)
Social entrepreneurship’s increasing reliance on crowdfunding to finance impact-driven businesses underscores the necessity for a more integrated scholarly approach in the literature. This study addresses the fragmented understanding of the intersection between social entrepreneurship and crowdfunding (SE-CF), a growing area with significant implications for financing social innovation. Using a bibliometric analysis of 120 publications from Scopus and Web of Science, the conceptual structure and emerging themes in SE-CF research are mapped. Findings reveal five thematic clusters and a scholarly interest surge since 2020. Theoretically, the study contributes by mapping the intellectual structure of research at the intersection of social entrepreneurship and crowdfunding, identifying underexplored themes such as governance and performance measurement. Managerially, the findings reveal perspectives that can inform the design of mission-aligned, impact-oriented crowdfunding initiatives. These findings support future research on transparency, hybrid models, and the cross-border scaling of social ventures